DIFFERENCES IN TEMPERATURE OF SOLAR COLLECTORS USING PAINT WITH A MIXTURE OF COCONUT SHELL CARBON AND PALM SHELL - Nereus Tugur Redationo; Bernardus Crisanto Putra Mbulu; Febri Valen Herwinsha (Mechanical, Energy and Material (METAL), 2023)
Coconut shell carbon and palm shell carbon which undergo a pyrolysis process at 1000oC were used as coatings for solar collectors. The two carbons were tested by SEM to determine their composition. Coconut shell carbon and palm shell carbon were mixed with paint as a coating on the aluminum surface of the solar collector. Aluminum alloy carbon paint was tested for temperature on the surface and bottom. The results of the SEM test, solar collector temperature test and discussion were the basis for knowing the carbon layer content of palm shells, coconut shells and without carbon layers. The results of the SEM test obtained the carbon content of palm shells 86.2% C and coconut shells 92.3% C. The results of the solar collector temperature test for 7 days, on the top surface of the palm shell was 3oC and the bottom surface was 0.9oC. High carbon content indicates a change in temperature in the solar collector.